2015
DOI: 10.1111/nmo.12524
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome: an integrated explanatory model for clinical practice

Abstract: It was possible to elucidate an integrated, three-component EM as a basis for clinicians to conceptualize the nature of IBS, with the potential to contribute to better diagnosis and management, and dialog with sufferers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 130 publications
(276 reference statements)
2
24
0
1
Order By: Relevance
“…Treatment concepts that target these psychosocial factors of patients with IBS should be based on evidence-based models that take the following three components into account: altered peripheral regulation of gut function, altered brain–gut signalling and reducing psychological distress, including general hypervigilance and a general mindset of catastrophizing 209 . Such models might be helpful as a basis of patient education and a target for effective treatments.…”
Section: Managementmentioning
confidence: 99%
“…Treatment concepts that target these psychosocial factors of patients with IBS should be based on evidence-based models that take the following three components into account: altered peripheral regulation of gut function, altered brain–gut signalling and reducing psychological distress, including general hypervigilance and a general mindset of catastrophizing 209 . Such models might be helpful as a basis of patient education and a target for effective treatments.…”
Section: Managementmentioning
confidence: 99%
“…This signal pathway leads to the augmentation symptomatic response in patients with IBS. A recent study suggested that intestinal microbiota and psychological distress at work were mediators of visceral hypersensitivity [9]. Based on these findings, there have been many attempts to improve IBS symptoms by the manipulation of intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main hypotheses behind the integrated explanatory model of IBS for clinical practice: altered peripheral regulation of gut function, altered brain gut signaling, and psychological distress. 34…”
Section: Pathogenesis and Pathophysiology Of Ibsmentioning
confidence: 99%
“…An altered peripheral regulation of gut function is triggered by changes in neurotransmitter signaling, GI inflammation, and GI microbial changes. 34 Specific peripheral mechanisms can result in symptoms of IBS. These mechanisms include: abnormal colonic transit and rectal evacuation, intraluminal irritants, inflammation, altered bile acid synthesis, and alterations in the GI microbiome.…”
Section: Altered Peripheral Regulation Of Gut Functionmentioning
confidence: 99%